2018
DOI: 10.1002/edm2.53
|View full text |Cite
|
Sign up to set email alerts
|

Progression of glucose‐lowering diabetes therapy in TECOS

Abstract: Summary Aims TECOS was a randomized, double‐blind, placebo‐controlled trial assessing the impact of sitagliptin vs. placebo on cardiovascular outcomes when added to usual care in patients with type 2 diabetes. We report the use of concomitant diabetes medications and the risk for progression to insulin during follow‐up. Materials and Methods TECOS enrolled 14 671 participants with HbA1c 6.5%‐8.0% on monotherapy with metformin, pioglitazone, sulfonylurea (SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A sensitivity analysis with first‐time users of DPP‐4 inhibitors as a comparator cohort was also carried out. This comparison allowed assessment of the effects of GLP‐1RAs and SGLT2 inhibitors versus a drug class—DPP‐4 inhibitors—known to exhibit neutral effects on major CV outcomes in T2D patients 33–36 ; moreover, GLP‐1RAs, SGLT2 inhibitors and DPP‐4 inhibitors are prescribed only by diabetes specialists in Italy.…”
Section: Methodsmentioning
confidence: 99%
“…A sensitivity analysis with first‐time users of DPP‐4 inhibitors as a comparator cohort was also carried out. This comparison allowed assessment of the effects of GLP‐1RAs and SGLT2 inhibitors versus a drug class—DPP‐4 inhibitors—known to exhibit neutral effects on major CV outcomes in T2D patients 33–36 ; moreover, GLP‐1RAs, SGLT2 inhibitors and DPP‐4 inhibitors are prescribed only by diabetes specialists in Italy.…”
Section: Methodsmentioning
confidence: 99%
“…However, treating blood glucose levels is not going to prevent the development of vascular pathology in diabetes. This was confirmed in seven multinational, multi-center, randomized controlled trials of tight blood glucose control with medications (ACCORD, ADVANCE, VADT, ORIGIN, ELIXA, TECOS and SAVOR) [10][11][12][13][14][15][16]. They all failed to demonstrate reductions in heart disease, the major cause of death of persons with diabetes [17].…”
Section: Resultsmentioning
confidence: 91%
“…Sixth, although some may argue that the outcome differences may have been driven by differences in concomitant medication use, we adjusted for use of aspirin, beta-blockers, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, statin, and glucose-lowering therapies in our multivariate models, <2.5% of patients were on thiazolidinediones or glucagon-like peptide-1 receptor agonists during the trial, none were taking a sodium-glucose co-transporter 2 inhibitor, and up-titration of glycaemic therapies largely occurred in patients with marked hyperglycaemia during follow-up (the mean HbA 1c when agents were added was 8.5%). 13 Thus, it would not alter our finding of a HbA 1c nadir of 7% but may have underestimated the magnitude of excess risk for patients with markedly elevated HbA 1c . In the same vein, given a prior TECOS sub-study demonstrated a U-shaped association between baseline blood pressure assessments and cardiovascular outcomes, 24 we adjusted for systolic blood pressure in our multivariable analyses.…”
Section: Medianmentioning
confidence: 81%
“…It is important to note that the association between HbA 1c levels and outcomes that we observed is not due to use of glucose-lowering therapies known to modify HF risk independent of glycaemic effects: less than 2.4% of TECOS participants were taking a thiazolidinedione or a glucagon-like peptide-1 receptor agonist, and none a sodium-glucose co-transporter 2 inhibitor. 4,13,14 While the meta-analysis of 12 cardiovascular outcome trials in T2D discussed in our Introduction reported no correlation between HbA 1c values and risk of HF events, 2 none of those trials specifically targeted HbA 1c reduction. For at least some of the agents with demonstrated cardiovascular efficacy in T2D, their impacts appear to be independent of their glucose-lowering effects.…”
Section: Medianmentioning
confidence: 98%